Аmelioration by phytoadaptogene of effects of balneofactors of Truskavets' Spa on patients with post-radiation encephalopathy - Walery Zukow (Kazimierz Wielki University, 2023)
Background. We have previously explored effects of Ukrainian phytocomposition "Balm Truskavets'" on parameters of neuro-endocrine-immune complex and biophotonics in humans with maladaptation. It is known that in patients with post-radiation encephalopathy the reaction to some stimuli is significantly changed, therefore it needs correction. The purpose of this study is to test the ability of this phytocomposition to amelioration the effects of standard balneotherapeutic complex in patients with post-radiation encephalopathy. Material and methods. The research was carried out through a retrospective analysis of the database of the Truskavetsian Scientific School of Balneology, which remained unpublished. The object of observation in 1997 were 19 men and 3 women with urate urolithiasis and chronic pyelonephritis who were exposed to pathogenic factors of the accident at the Chоrnobylian nuclear power plant during the liquidation of its consequences in 1986-87. The survey was conducted twice: on admission and after two weeks of rehabilitation in sanatorium "Perlyna Prykarpattya" (Truskavets' Spa). 11 patients received standard balneotherapy while the other 11 patients additionally received the phytocomposition "Balm Truskavets'". According to the protocol, blood pressure, routine hematological and biochemical blood parameters were determined. In addition, physical working capacity (PWC150) as well as EEG, heart rate variability (HRV) and immunity parameters were determined. Results. Standard balneotherapy increases the decreased level of T-helper lymphocytes, but further decreases the level of B-lymphocytes, glomerular filtration rate and PWC150, in combination with increased normal levels of blood creatinine and urea, as well as decreased levels of diastolic BP and heart rate. This is accompanied by a further increase in the sympathetic tone and the leveling of the increased of ULF band HRV as marker of level in the plasma of catecholamines and glucocorticoids. Additional use of phytocomposition limits the adverse effects of standard balneotherapy by modulating EEG and HRV parameters. Conclusion. Phytocomposition "Balm Truskavets'" by modulating the parameters of the nervous system limits the adverse effects of standard balneotherapy at the Truskavets' Spa in patients with post-radiation encephalopathy.